2017
DOI: 10.1038/s41598-017-12258-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of a newly-identified entry pathway into the malaria parasite-infected erythrocyte to inhibit parasite egress

Abstract: While many parasites develop within host cells to avoid antibody responses and to utilize host cytoplasmic resources, elaborate egress processes have evolved to minimize the time between escaping and invading the next cell. In human erythrocytes, malaria parasites perforate their enclosing erythrocyte membrane shortly before egress. Here, we show that these pores clearly function as an entry pathway into infected erythrocytes for compounds that inhibit parasite egress. The natural glycosaminoglycan heparin sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 67 publications
(82 reference statements)
0
46
0
1
Order By: Relevance
“…However, repeated attempts to generate an EXP2–BioID fusion with a verified CRISPR/Cas9 strategy for editing the 3′ end of exp2 were unsuccessful. Endogenous EXP2 can tolerate a monomeric NeonGreen (mNG, 27 kDa) fusion without an obvious fitness cost (Glushakova et al, ); thus, the bulkier size (35 kDa) or enzymatic activity of BioID may interfere with EXP2 trafficking or essential functions. To test the former possibility, we next attempted fusion with the second generation BioID2 derived from Aquifex aeolicus (Figure S1a).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, repeated attempts to generate an EXP2–BioID fusion with a verified CRISPR/Cas9 strategy for editing the 3′ end of exp2 were unsuccessful. Endogenous EXP2 can tolerate a monomeric NeonGreen (mNG, 27 kDa) fusion without an obvious fitness cost (Glushakova et al, ); thus, the bulkier size (35 kDa) or enzymatic activity of BioID may interfere with EXP2 trafficking or essential functions. To test the former possibility, we next attempted fusion with the second generation BioID2 derived from Aquifex aeolicus (Figure S1a).…”
Section: Resultsmentioning
confidence: 99%
“…To monitor EXP2 distribution in unfixed EXP1 apt parasites, we introduced a C ‐terminal mNG fusion on the endogenous copy of EXP2 and imaged parasites at a late stage corresponding with developmental arrest. Live fluorescent analysis of a parental EXP2–mNG control line with an unmodified exp1 locus (Glushakova et al, ) showed a punctate distribution at early stages that often resolved into several larger patches in trophozoites and schizonts (Figure 6a). In contrast, EXP2 distribution was substantially altered in EXP1 apt ::EXP2‐mNG parasites, often concentrating into one or two discrete points along the PVM (Figure 6a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations